P-149 Increasing recognition and support for all in or around the last year of life, airedale's experience. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Wilson, Linda; Procter, Elizabeth
Abstract : In Airedale, we have been developing end of life care services at a population level, aiming to identify, offer sensitive conversations, document end of life preferences via an EPaCCS template and coordinate care from a 24/7 hub based at an acute hospital (Gold Line). In 2017/18, 76% of all 'non-sudden' deaths (56% all deaths) were supported by Gold Line (assuming 25% deaths are not preceded by a phase where identification is possible). Training for health professionals in serious illness conversations has been provided, partly via the NHS England Serious Illness Conversation pilot. Of the patients who were identified as being in the last year (or so) of life, 14% died in hospital, 69% in their usual place of residence and 74% in the preferred place of death. Airedale has the lowest % of all deaths in hospital in England (33.4% cf 46.2%). 78% of patients registered to the service have a non-cancer diagnosis and 76% are NOT known to specialist palliative care services. 42% have a dementia code in their record and 70% are aged 80 or over. Data from the End of Life Intelligence Network shows that in 2015, 69% of all deaths were on a GP palliative care register and only 4.8% patients who died had three or more acute hospital admissions in the last 90 days of life (England 6.9%). Figures are likely to have improved further since then. Our service is offering coordinated support 24/7 to a large proportion of people dying who are not being supported by specialist palliative care services. High levels of satisfaction are expressed by patients, their carers and professionals. We believe that the provision of a 24/7 support and advice line, supported by an EPaCCS template is helping to encourage identification and thus improve outcomes for many more patients and their families in line with their expressed preferences and in a cost effective way.